Health Limitations, Regional Care Infrastructure and Wellbeing in Later Life: A Multilevel Analysis of 96 European Regions - Alina Schmitz; Martina Brandt (Social Indicators Research, 2022)
Background: In light of rapid population ageing across Europe, maintaining a high level of wellbeing in old age is a priority for social policy. Research on macro-level influences on wellbeing in the older population is rare, especially regarding heterogeneous effects within different groups, such as persons with and without health limitations. Objective: The purpose of this study is to shed light on the following questions: Is the regional availability of care infrastructure crucial for the wellbeing in later life? If so, does the relevance of care infrastructure differ depending on an individual's health status? Methods Data were drawn from wave 6 of the Survey of Health, Ageing and Retirement in Europe (SHARE) matched with data on the number of long-term care (LTC) beds on the regional level. We estimated multilevel regression models, including a cross-level interaction between individual health needs and regional LTC beds. Results Our analyses show that the number of LTC beds is related to the wellbeing, as measured by overall life satisfaction, in the population aged 500.167em+0.167emyears. The association is more pronounced for individuals with health limitations who might be in need of such infrastructure. Conclusions Communities and local governments should ensure the necessary infrastructure for older individuals in need of care and help across different regions. The availability of formal care services may be perceived a "safety net" and thus improve wellbeing, but future studies need to investigate the underlying mechanisms.
Keywords: 300; Life satisfaction; Long-term care beds; Macro-level influences; SHARE; Old age; NUTS-2